Coexistence of territorial competitor ants in fragmented boreal forest landscape - Sorvari, Jouni; Huhta, Esa; Hakkarainen, Harri (Springer, 2025)
The distribution of species in a patchy habitat may be influenced by competitive interactions. The dominant and highly competitive boreal ant species belong to the Formica rufa group. A pair of species, Formica aquilonia and Formica polyctena, require extensive territories due to their multi-nest breeding habits. The coexistence and habitat patterns of these two wood ant species in the boreal forest landscape were investigated. Forest characteristics in the vicinity of nests in forest patches were similar for both species, but they did not coexist in the same sampling plots of 0.79 ha in forest patches, indicating competitive exclusion. The sampling plots in large forest patches were more occupied by F. aquilonia, while no such association was found for F. polyctena. At a larger spatial scale (78.5 ha), we found that F. polyctena was more tolerant of smaller forest patches than F. aquilonia suggesting that these two ant species can coexist in moderately fragmented forest landscapes. However, forest habitat loss, fragmentation and climate-induced changes in forest tree structure may shift the species balance in favour of F. polyctena over F. aquilonia in the future.